The End of Blasphemy Crimes in Indonesia: Shifts in Human Rights Limitations and MUI’s Fatwa Authority - Tobroni, Faiq; Tahir, Ach; Iswantoro; Basuki, Udiyo; Murdoko (Faculty of Law, Universitas Pasundan, 2025)
The old Indonesian Criminal Code poses problems with regard to the handling of religious crimes. For example, Article 156a criminalises religious expressions considered deviant or heretical. The old Criminal Code limits religious expression by criminalising heretical religious interpretations. These limitations obscure the freedom of religion as a human right. This study examines the paradigm shift in human rights limitations in the new Criminal Code, and its impact on the fatwa authority of the Indonesian Ulema Council (MUI). A normative juridical method is employed through a literature-based analysis of statutory provisions on blasphemy offences under both the former Indonesian Criminal Code and the new 2023 Indonesian Criminal Code, alongside fatwas issued by the Indonesian Ulema Council (MUI) and relevant legal and human rights scholarship. The findings demonstrate that Article 300 of the new Criminal Code reconfigures the regulation of blasphemy offences by shifting the framework of limitations on human rights of religious expression, particularly through changes in the scope of criminalisation and the normative role of the fatwa authority. Criminalisation now applies to actions that interfere with freedom of religion, rather than to blasphemy against religion itself. The objective of limitation has shifted from protecting religion to protecting religious freedom. This change has implications for the role of local fatwa authorities in handling religious crimes.